Cutaneous candidiasis mimicking acute generalized exanthematous pustulosis: A case report - Emily Seale; Alison Spurr; Iris Teo; Steven J Glassman (SAGE Open Medical Case Reports, 2023)
Disseminated cutaneous candidiasis is a rare manifestation of candidiasis that arises most commonly from Candida albicans . It is described as a widespread erythematous papulopustular skin infection that typically affects premature newborns or immunocompromised patients. While candidal infections usually respond well to antifungal therapy, the clinical presentation of disseminated cutaneous candidiasis can often mimic a variety of other dermatologic conditions, that can lead to delayed diagnosis and treatment. We present a 67-year-old comorbid male patient with widespread erythema and superficial pustules resembling acute generalized exanthematous pustulosis (AGEP) that was actually an unexpected manifestation of disseminated cutaneous candidiasis. Prompt initiation of a topical and oral antifungal regimen contributed to marked improvement. Given the high frequency of drug eruptions in comorbid patients receiving multiple medications, alternate diagnoses like infections should be included in the differential diagnosis.